Implications of Security Market Data for Models of Dynamic Economies - Hansen, Lars Peter; Jagannathan, Ravi (Journal of Political Economy, 1991)
The authors show how to use security market data to restrict the admissible region for means and standard deviations of intertemporal marginal rates of substitution of consumers. Their approach (1) is nonparametric and applies to a rich class of models of dynamic economics; (2) characterizes the duality between the mean-standard deviation frontier for intertemporal marginal rates of substitution and the familiar mean-standard deviation frontier for asset returns; and (3) exploits the restriction that intertemporal marginal rates of substitution are positive random variables. The region provides a convenient summary of the sense in which asset market data are anomalous from the vantage point of intertemporal asset pricing theory. Copyright 1991 by University of Chicago Press.